Evaluation of SIMPUS Using the Technology-to-Performance Chain Model at the Bogor City Health Center - Kadarisman, Aris (Poltekkes Kemenkes Semarang, 2025)
The Health Center Management Information System (SIMPUS) is a regional health information system of the Bogor City Health Office that has been used since 2014 until now. This study aims to evaluate the use of SIMPUS at the Bogor City Health Center using the Technology-to-Performance Chain model. The research was conducted from April to June 2024 at Bogor City Health Center. The type of research used quantitative research methods with a cross sectional design. The study population was 533 SIMPUS users consisting of the Admin / Medical Recorder Technician, Nurses, General Practitioners, Dentists, Midwives and Pharmacy Officers of the Bogor City Health Center with a sample size of 90 officers. Data collection using a questionnaire with variables of Task-characteristics, Technology-characteristics, Task-technology Fit, Utilization and Performance Impact with a Likert scale of 1-4 where 1 (strongly disagree) and 4 (strongly agree). Data analysis with Partial Least Square Structrual Equation Modeling (PLS-SEM). The results showed that most of the 90 respondents were female in the age range of 26 to 35 years old with bachelor’s degree. Task-characteristics and Technology-characteristics have a positive and significant effect on Task-technology Fitit. Task-Technology Fit has a positive and significant effect on Utilization and Performance Impact. Utilization has a positive and significant effect on Performance Impact.